Extended Pancreas Donor Program - the EXPAND study: a prospective multicenter trial testing the use of pancreas donors older than 50 years - Proneth, Andrea; Schnitzbauer, Andreas A.; Schenker, Peter; Wunsch, Andreas; Rauchfuss, Falk; Arbogast, Helmut; Manekeller, Steffen; Nadalin, Silvio; Heise, Michael; Ströhlein, Michael A.; Banas, Bernhard; Schemmer, Peter; et al. (Transplantation, 2018)
Background - Pancreas transplantation is the only curative treatment option for patients with juvenile diabetes. Organ shortage and restrictive allocation criteria are the main reasons for increasing waitlists, leading to severe morbidity and mortality. We designed a study to increase the donor pool with extended donor criteria (EDC) organs (donor age, 50-60 years; body mass index, 30-34 kg/m2). - Methods - Utilization of EDC organs required the implementation of a new allocation system within Eurotransplant. The study was a prospective, multicenter, 2-armed trial. The primary endpoint was pancreas function after 3 months. Rejection episodes, kidney function, and waitlist time were secondary endpoints. Patients receiving an EDC organ were study group patients; recipients of standard organs were control group patients. Follow-up was 1 year. - Results - Seventy-nine patients were included in 12 German centers, 18 received EDC organs and 61 received standard organs. Recipient demographics were similar. Mean EDC donor age was 51.4 ± 5 years versus 31.7 ± 12 in the control group. Insulin-free graft survival was 83.3% for EDC and 67.2% for standard organs (P = 0.245) after 3 months. One-year pancreas survival was 83.3% and 83.5% in the EDC versus standard group. One-year kidney allograft survival was approximately 94% in both groups. Rejection episodes and morbidity were similar. - Conclusions - The Extended Pancreas Donor Program (EXPAND) shows in a prospective trial that selected EDC organs of donors older than 50 years can be used with outcomes similar to standard-criteria organs, therefore showing potential to reduce organ shortage and waiting times. This study substantiates the full implementation of EDC organs in a pancreas allocation system.
Gesehen am 26.08.2020